Effects of compositional heterogeneity and spatial autocorrelation on richness and diversity in simulated landscapes - Tardanico, Joseph; Hovestadt, Thomas (Ecology and evolution, 2023)
Landscape structure plays a key role in mediating a variety of ecological processes affecting biodiversity patterns; however, its precise effects and the mechanisms underpinning them remain unclear. While the effects of landscape structure have been extensively investigated both empirically and theoretically from a metapopulation perspective, the effects of spatial structure at the landscape scale remain poorly explored from a metacommunity perspective. Here, we attempt to address this gap using a spatially explicit, individual‐based metacommunity model to explore the effects of landscape compositional heterogeneity and per se spatial configuration on diversity at the landscape and patch levels via their influence on long‐term community assembly processes. Our model simulates communities composed of species of annual, asexual organisms living, reproducing, dispersing, and competing within grid‐based, fractal landscapes that vary in their magnitude of spatial environmental heterogeneity and in their degree of spatial environmental autocorrelation. Communities are additionally subject to temporal environmental fluctuations and external immigration, allowing for turnover in community composition. We found that compositional heterogeneity and spatial autocorrelation had differing effects on richness, diversity, and the landscape and patch scales. Landscape‐level diversity was driven by community dissimilarity at the patch level and increased with greater heterogeneity, while landscape richness was largely the result of the short‐term accumulation of immigrants and decreased with greater compositional heterogeneity. Both richness and diversity decreased in variance with greater compositional heterogeneity, indicating a reduction in community turnover over time. Patch‐level richness and diversity patterns appeared to be driven by overall landscape richness and local mass effects, resulting in maximum patch‐level richness and diversity at moderate levels of compositional heterogeneity and high spatial autocorrelation. The role of landscape spatial structure in shaping biodiversity patterns remains poorly explored from a metacommunity perspective. We used an individual‐based metacommunity model to investigate the effects of compositional heterogeneity and spatial configuration on biodiversity via their effects on community assembly. We show that different degrees of compositional heterogeneity and spatial autocorrelation result in different assembly processes predominating and that richness and diversity are shaped by different processes at the landscape and patch scales, resulting in differing responses to compositional heterogeneity and spatial autocorrelation at different scales.